The microeconomic mode : political subjectivity in contemporary popular aesthetics - Elliott, Jane, 1969- (Columbia University Press, 2018)
"Much as realism was born out of an attempt to understand and depict the world and the individual's place in it during the rise of industrial capitalism, Jane Elliott argues that the 'microeconomic mode' represents an attempt to understand subjectivity in the current economic moment. Elliott reveals how different films, novels, and television shows reflect the contemporary moment by adopting a mode of storytelling, focused on individualistic choice but one that is severly limited. Examples can be seen in the choices and options open to characters in works ranging from 127 Hours to The Road to The Hunger Games. Discussing such works as Gone Girl, the Saw film franchise, and television shows such as Survivor and Fear Factor, Elliott considers depictions in which the capacity to make decisions for oneself becomes a burden--an exercise in suffering--rather than conforming to the rhetoric of neoliberalism that celebrates agency. She suggests that the growing prevalence of this popular form offers a way to imagine personal agency as the problem, rather than the solution"--